The Southern Hemisphere Blocking Index in the ERA5 and the NCEP/NCAR Datasets: A Comparative Climatology for the Period 1940–2022 - Yuchechen, Adrian E. (2025)
Fil: Yuchechen, Adrian E. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina